Prussian‐Blue Catalysis and NFC Synergy: a Battery‐Free Laser‐Induced Graphene‐Based Platform for Urine Glucose Monitoring at Point‐of‐Care - Sinan Uzunçar; Gabriel Maroli; Massimo Urban; Arben Merkoçi (Advanced Science)
Abstract Prussian‐blue nanoparticles (PBNPs) show promise in electrochemical hydrogen peroxide (H2O2) sensing but face operational stability challenges without complex strategies. This study introduces a simplified, polymer‐based synthesis method, enhancing their stability in a single step. Chemical polymerization of Prussian‐blue (PB) and poly(3,4‐ethylenedioxythiophene) (PEDOT) with gelatin as a polycationic soft template yields a self‐assembled PB‐infused Catalytic Hetero‐interface Architecture (PB‐CHIA) that remarkably improves the stability of PBNPs and offers functional groups for enzyme immobilization, supporting robust biosensing applications. The softened PEDOT rigidity extends PB‐CHIA's applicability to various carbonaceous electrode substrates, including glassy carbon and laser‐induced graphene (LIG) via simple drop‐casting. A fluidic cell module designed with the optimized LIG morphology (nano‐fibrous fringes, LIG‐F, diameter: 72.87 ± 12.24 nm) modified with PB‐CHIA and glucose oxidase enables non‐invasive urine glucose monitoring. The configuration accurately quantifies glucose within a linear range of 10–400 µM [R2: 0.991, Sensitivity: 29.88 ± 4.98 µA mM⁻¹ cm⁻2, Detection Limit: 4.52 ± 2.24 µM], covering medical needs. A near‐field communication potentiostat is devised for a fully integrated, batteryless, wireless point‐of‐care (POC) prototype, enabling rapid smartphone readouts in 15 s for daily home‐based use. The stable operation of PB‐CHIA allows working electrodes’ scalable production, highlighting its potential for diverse POC devices in urinary analysis reliant on H2O2 assays.